2006
DOI: 10.4269/ajtmh.2006.75.1003
|View full text |Cite
|
Sign up to set email alerts
|

Catacamas Virus, a Hantaviral Species Naturally Associated With Oryzomys Couesi (Coues’ Oryzomys) in Honduras

Abstract: Abstract. The primary objective of this study was to extend our knowledge of the geographical distribution, genetic diversity, and natural host associations of the hantaviruses indigenous to North America. Antibody to a hantavirus was found in 5 (20.8%) of 24 Coues' oryzomys (Oryzomys couesi) and none of 41 other rodents captured near the town of Catacamas in eastern Honduras, and a hantavirus was isolated from one of the antibody-positive Coues' oryzomys. Analyses of nucleotide and amino acid sequence data in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 44 publications
(56 reference statements)
0
22
0
1
Order By: Relevance
“…are members of the family Cricetidae, subfamily Sigmodontinae (Musser and Carleton 2005). Alston's cotton rat (S. hispidus) in western Venezuela is the principal host of CADV (Fulhorst et al 1997), the hispid cotton rat in northern Texas is the putative principal host of MULV (Rawlings et al 1996), Coues' rice rat (Oryzomys couesi) in Honduras is the principal host of CATV (Milazzo et al 2006), the fulvous pygmy rice rat (O. fulvescens) in Panama is the principal host of CHOV (Vincent et al 2000), a pygmy rice rat (Oligoryzomys spp.) in western Venezuela is the principal host of MAPV (Fulhorst et al 2004), and as indicated previously, the hispid cotton rat in southern Florida, marsh rice rat in the southeastern United States, and long-tailed pygmy rice rat in Argentina and Chile are the principal hosts of BCCV, BAYV, and ANDV, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…are members of the family Cricetidae, subfamily Sigmodontinae (Musser and Carleton 2005). Alston's cotton rat (S. hispidus) in western Venezuela is the principal host of CADV (Fulhorst et al 1997), the hispid cotton rat in northern Texas is the putative principal host of MULV (Rawlings et al 1996), Coues' rice rat (Oryzomys couesi) in Honduras is the principal host of CATV (Milazzo et al 2006), the fulvous pygmy rice rat (O. fulvescens) in Panama is the principal host of CHOV (Vincent et al 2000), a pygmy rice rat (Oligoryzomys spp.) in western Venezuela is the principal host of MAPV (Fulhorst et al 2004), and as indicated previously, the hispid cotton rat in southern Florida, marsh rice rat in the southeastern United States, and long-tailed pygmy rice rat in Argentina and Chile are the principal hosts of BCCV, BAYV, and ANDV, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Provisional species in the genus Hantavirus include Catacamas virus (CATV) (Milazzo et al 2006), Choclo virus (CHOV) (Vincent et al 2000), and Maporal virus (MAPV) (Fulhorst et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for this ancient relationship includes the association of phylogenetically closely related hantaviral species with phylogenetically closely related, allopatric rodent species. For example, Bayou virus with the marsh oryzomys (Oryzomys palustris) in the southeastern United States (Ksiazek et al 1997), Catacamas virus with Coues' oryzomys (Oryzomys couesi) in Honduras (Milazzo et al 2006), and Playa de Oro virus with the Mexican oryzomys (Oryzomys mexicanus) in western Mexico (Chu et al 2008). …”
mentioning
confidence: 99%
“…18,19 Spillover and host switching could explain the infection of two different species: the ecology and respective reservoir performance of Z. brevicauda and O. fulvescens should be scrutinized. Considering that Z. brevicauda and O. fulvescens have already been identified as competent reservoirs of different hantaviruses 20,21 and that it is now accepted that a single hantavirus strain can infect different rodent species, [22][23][24] our results suggest that Maripa may be present in a rodent's community of diverse sympatric and/or syntopic competence at the same collection site.…”
mentioning
confidence: 88%